THE ARCTIC HUB—REGIONAL AND GLOBAL PERSPECTIVES - Arkady Tishkov; Rachold Volker (Geography, Environment, Sustainability)
THE ARCTIC HUB—REGIONAL AND GLOBAL PERSPECTIVES(THE ARCTIC SCIENCE SUMMIT WEEK, ASSW—2013)